Dichotomitin promotes osteoblast differentiation and improves osteoporosis by inhibiting oxidative stress - Meichun Han; Weibin Du; Lei Zhang; Zhenwei Wang; Shengqiang Fang; Yang Zheng; Renfu Quan (Journal of Orthopaedic Surgery and Research)
Abstract Objective Osteoporosis is a systemic disease with high morbidity and significant adverse effects. Increasing evidence supports the close relationship between oxidative stress and osteoporosis, suggesting that treatment with antioxidants may be a viable approach. This study evaluated the antioxidant properties of dichotomitin (DH) and its potential protective effects against osteoporosis. Methods SD rats were divided into three groups: Sham, OVX, and OVX + DH (5 mg/kg, intraperitoneal injection twice weekly). After three months, blood samples, femurs, and tibiae were collected for analysis. Micro-CT evaluated the femoral, while histological examination assessed tibial tissues. Serum osteogenic biochemical markers were measured. In vitro, osteogenic differentiation was induced with varying concentrations of DH, followed by ALP and ARS staining. RT-qPCR and western blot were used to assess the expression of osteogenesis-related genes and proteins. Additionally, an oxidative stress cell model was established, dividing cells into control, H2O2-treated, and H2O2 + DH-treated groups. Expression of oxidative stress-related genes and proteins was assessed using real-time quantitative PCR and western blotting. Results Micro-CT and histological staining revealed decreased and disrupted bone trabeculae in the OVX group, whereas the DH-treated group exhibited enhanced bone trabecular area and structure compared to the OVX group. In vitro studies showed that DH enhanced ALP activity and elevated expression of RUNX2, OPN, OCN, SOD1, and SOD2. Conclusion DH has the potential to enhance osteoblast differentiation and alleviate osteoporosis through the attenuation of oxidative stress.